Isolation Of heterocyclic hydrocarbons from seawater - Wong, Ha Chung (Universiti Malaysia Sarawak (UNIMAS), 2013)
Heterocyclic hydrocarbons are widely distributed in soils and sediments, groundwater, atmosphere, and marine environment. They are very stable organic compounds that persist in environment for long period of time. The presence of heterocyclic hydrocarbon in the seawater due to the industrial process and spillage of petroleum causes the pollution to the marine environment and may affect human health. Bioremediation is one of the solutions to degrade the heterocyclic hydrocarbon. It involves the activity of microorganisms that oxidizes the aromatic ring of the heterocyclic hydrocarbon and degrades it. The degrading bacteria that isolated from the seawater are useful to clean up the heterocyclic hydrocarbon in seawater. This study aims to isolate heterocyclic hydrocarbon degrading bacteria from the coast of Sarawak. Five bacteria were isolated and characterized via biochemical tests and molecular technique. The degradation ability of the isolated bacteria was determined by testing the chemical properties for each bacterium. The result shows that the isolated bacteria may play some role in heterocyclic hydrocarbon degradation.